Analisis Peran Guru sebagai Agen Perubahan disekolah dan Masyarakat (Al-Ilmiya: Jurnal Pendidikan Islam, 2025)
Teachers have a strategic role not only as educators in the school environment, but also as agents of change in society. This study aims to analyze the role of teachers in schools and society, the obstacles they face, and strategies to strengthen their function as agents of change. Using a descriptive qualitative method with a literature study approach, this study examines various related journals and references. The results show that teachers play an important role in character development, moral values formation, and mastery of various intelligences of students according to Howard Gardner's theory. In society, teachers are expected to be role models and drivers of social education. However, this role is constrained by limitations in teacher competence, lack of facilities, conventional teaching habits, and resistance from traditional communities. Strategies to enhance the role of teachers include training in motivation and personality, mastery of learning technology, and strengthening cooperation among teachers within an educational unit. Thus, teachers can optimally carry out their role in educating the nation and encouraging positive social transformation.